Spatial and Time Pattern Distribution of Water Birds Community at Mangrove Ecosystem of Bengawan Solo Estuary - Gresik Regency - Sutopo .; Nyoto Santoso; Jarwadi Budi Hernowo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Mangrove ecosystem in Bengawan Solo estuary is a part of the essential ecosystem and also as important and endemic birds’ areas. Aim of this study is to analysis the parameter of habitat condition, analysis the different of time and spatial pattern and provide the management strategy for water birds and habitat. Reseach was carry out at January – May, 2017 (two period observation). Methods are used i.e. concentration count, single and unit plot, point count, interview and field observation. Data analyze using chi-square, grid-line point and mark point, beak-type and vegetation analysis. There are 41 (forty one) species of water birds (23 migrant species and 17 native species). Chi-square analysis have significance difference both the time and spatial and also type of feed with chi-square values (χ2 hit.(2;0,95) > χ2 tab.(2;0,95). Migrant birds’ occupy the mudflat for feeding and resting ground, while the native birds use pond areas. Common the invertebrate species as feed for migrant like crustace and native birds are tend to feed fish and shrimp. Feeding and resting activities by migrant birds was influence by water-tidal condition. Total of water birds population are 112.100+ individual. Total of mangrove species was identified are 15 (fifteen) species, and dominant at three habitus by Avicennia alba.Keywords: Bengawan Solo Estuary, mangrove ecosystem, spatial and time, water birds